(untitled) (Revista Educação, Artes e Inclusão, 2021)
The following article has the purpose of discussing the teaching of art practiced in the region of the potiguar Seridó, in the Brazilian sertão, based on process documents produced in the teaching exercise in visual arts, during the development of na artistic and cultural intervention project, with emphasis on the study of the stencil, in a public state school of Caicó-RN. We understand process documents as the traces left behind produced during the creational process (SALLES, 2009, p.21), be it the artist or the art educator. It leaves, in his professional exercise, marks of its creative path with the students. The work curates the documents accompanying their processes, (PASSOS, etal, 2009), focusing on the collaborative Productions of knowledge, while following the most recente epistemological orientations, as we realize in BARBOSA, 2005, 2009; IAVELBERG, 2003, 2017; MARTINS, 2009; FERRAZ & FUSARI, 2009, 1993. The records of the teaching practices related to Arts are of huge importance to the development of creativity, the increase of the perception and the improvement of the pedagogical doing in this area of knowledge.